Direct visualization of location and uptake of applied melatonin and serotonin in living tissues and their redistribution in plants in response to thermal stress. Issue 1 (20th October 2018) - Erland, Lauren A. E.; Yasunaga, Adam; Li, Isaac T. S.; Murch, Susan J.; Saxena, Praveen K.
Abstract: Melatonin and serotonin are important phytochemicals enabling plants to redirect growth in response to environmental stresses. Despite much research on their biosynthetic routes, localization of their biosynthetic enzymes and recent identification of a phytomelatonin receptor, localization of the molecules themselves has to date not been possible. Elucidation of their locations in living tissues can provide an effective tool to facilitate indolamine research across systems including both plants and animals. In this study, we employed a novel technique, quantum dot nanoparticles, to directly visualize melatonin and serotonin in axenic roots. Melatonin was absorbed through epidermal cells, travelled laterally, and accumulated in endodermal and rapidly dividing pericycle cells. Serotonin was absorbed by cells proximal to the crown with rapid polar movement toward the root tip. Thermal stress disrupted localization and dispersed melatonin and serotonin across cells. These data demonstrate the natural movement of melatonin and serotonin in roots directing cell growth and suggest that plants have a mechanism to disperse the indolamines throughout tissues as antioxidants in response to environmental stresses.